Anomalous Dimensionality‐Driven Phase Transition of MoTe2 in Van der Waals Heterostructure. (15th September 2021) - Ryu, Huije; Lee, Yangjin; Kim, Hyun‐Jung; Kang, Seoung‐Hun; Kang, Yoongu; Kim, Kangwon; Kim, Jungcheol; Janicek, Blanka E.; Watanabe, Kenji; Taniguchi, Takashi; Huang, Pinshane Y.; Cheong, Hyeonsik; et al.
Abstract: Phase transition in nanomaterials is distinct from that in 3D bulk materials owing to the dominant contribution of surface energy. Among nanomaterials, 2D materials have shown unique phase transition behaviors due to their larger surface‐to‐volume ratio, high crystallinity, and lack of dangling bonds in atomically thin layers. Here, the anomalous dimensionality‐driven phase transition of molybdenum ditelluride (MoTe2 ) encapsulated by hexagonal boron nitride (hBN) is reported. After encapsulation annealing, single‐crystal 2H‐MoTe2 transformed into polycrystalline Td ‐MoTe2 with tilt‐angle grain boundaries of 60°‐glide‐reflection and 120°‐twofold rotation. In contrast to conventional nanomaterials, the hBN‐encapsulated MoTe2 exhibit a deterministic dependence of the phase transition on the number of layers, in which the thinner MoTe2 has a higher 2H‐to‐Td phase transition temperature. In addition, the vertical and lateral phase transitions of the stacked MoTe2 with different crystalline orientations can be controlled by inserted graphene layers and the thickness of the heterostructure. Finally, it is shown that seamless Td contacts for 2H‐MoTe2 transistors can be fabricated by using the dimensionality‐driven phase transition. The work provides insight into the phase transition of 2D materials and van der Waals heterostructures and illustrates a novel method for the fabrication of multi‐phase 2D electronics. Abstract : Dimensionality‐driven anomalous phase transition of MoTe2 is demonstrated. The thinner MoTe2 has a higher 2H‐to‐Td phase transition temperature with distinct temperature differences. Vertical and lateral phase‐patterning is achieved by modulating the thickness via stacking and insertion of graphene. By using dimensionality‐driven phase transition, seamless Td contacts for 2H‐MoTe2 transistors are fabricated, leading to low contact resistance and high mobility.